GEOLOGI ALUVIUM DAN KARAKTER ENDAPAN PANTAI/PEMATANG PANTAI DI LEMBAH KRUENG ACEH, ACEH BESAR (PROV. NAD) - Moechtar, Herman; Subiyanto, Subiyanto; Sugianto, D. (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The alluvium in the Krueng Aceh valley, suggests that it is deposited in floodbasin, fluvial system, transition, and linier clastic environments. The linier clastic enviroments consists of offshore (Fellp), nearshore (Fedp), beach/ beach-ridge (Fep/ Fepp), and marsh deposits. The research was carried out by surface geological mapping and analysed sedimentology and stratigraphy of ten boreholes trending west-east to southwest and west-east to south. Depths of the boreholes varies from 2.30 to 10 m at elevation of + 0.90 - + 10 m above sea level. Based on correlation of sedimentary environment in the linier clatic environment,sea level changes can be divided into three cycles that were controlled by active tectonic of the Seulimeum fault respectively. Keywords: sedimentology, stratigraphy, alluvium